2013
DOI: 10.1016/j.socscimed.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Getting doctors into the bush: General Practitioners' preferences for rural location

Abstract: A key policy issue in many countries is the maldistribution of doctors across geographic areas, which has important effects on equity of access and health care costs. Many government programs and incentive schemes have been established to encourage doctors to practise in rural areas. However, there is little robust evidence of the effectiveness of such incentive schemes. The aim of this study is to examine the preferences of general practitioners (GPs) for rural location using a discrete choice experiment. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 38 publications
4
81
0
Order By: Relevance
“…For instance, Matsumoto et al identified commercial land price in a region as a factor (34); Ricketts and Randolph as well as Kassak et al identified the factor of urban development (35,38), and Isabel and Paula identified income geography (33) as significant factors. Other studies have similar findings, indicating that service location status and level of development are affecting factors (6,8,19,39,40,48).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…For instance, Matsumoto et al identified commercial land price in a region as a factor (34); Ricketts and Randolph as well as Kassak et al identified the factor of urban development (35,38), and Isabel and Paula identified income geography (33) as significant factors. Other studies have similar findings, indicating that service location status and level of development are affecting factors (6,8,19,39,40,48).…”
Section: Discussionmentioning
confidence: 58%
“…2017; 19(2):e40032. include quality of life in the service location (37); the gender, university of medical study, and local residency of the GP (native); the number of healthcare visits per week and the average time spent per visit; the GPs' income, schedule, and working hours; and educational and promotion opportunities (8,19,20,36,38,41,43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations